STUDENT STRATEGIES IN UNDERSTANDING CONTENT KNOWLEDGE OF RELIGIOUS MODERATION BASED ON ACADEMIC BACKGROUND - Syihabuddin, Syihabuddin; Maulani, Hikmah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to examine the strategies used by students in understanding content knowledge in the field of religious moderation. To achieve this goal, a case study method involving 150 students from the Universitas Pendidikan Indonesia (UPI) in the fields of language, vocational, and social studies was used. The data collection technique used was through questionnaires about the strategies used by students in understanding religion or religious moderation, and an attitude scale instrument to determine students' views on understanding strategies or knowledge acquisition. The results of the statistical analysis will be discussed, examined for trends, and compared with previous research findings or opinions. After the discussion, this study concludes that the most commonly used strategy by students is attending religious studies and engaging in discussions with individuals considered to have a better understanding of religion.